2017
DOI: 10.1371/journal.pone.0173384
|View full text |Cite
|
Sign up to set email alerts
|

Rapid on-line detection and grading of wooden breast myopathy in chicken fillets by near-infrared spectroscopy

Abstract: The main objective of this work was to develop a method for rapid and non-destructive detection and grading of wooden breast (WB) syndrome in chicken breast fillets. Near-infrared (NIR) spectroscopy was chosen as detection method, and an industrial NIR scanner was applied and tested for large scale on-line detection of the syndrome. Two approaches were evaluated for discrimination of WB fillets: 1) Linear discriminant analysis based on NIR spectra only, and 2) a regression model for protein was made based on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 20 publications
5
59
0
Order By: Relevance
“…Similar findings have been observed in chicken breast with WB myopathy (with or without WS). Several authors have reported consistent results including significant reduction in protein and ash contents and increase in moisture and lipid levels in WB muscles compared to their normal counterpart (Cai et al, 2018;Soglia et al, 2016a,b;Wold et al, 2017). The collagen content in the WB, SM, WB, WS/WB, and WS/SM presented contrasting results since some studies showed a higher content than the normal group and others did not observe a significant difference (Baldi et al, 2018;Cai et al, 2018;Soglia et al, 2016a,b).…”
Section: Physical-chemical Modifications In Abnormal Chicken Breastsmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar findings have been observed in chicken breast with WB myopathy (with or without WS). Several authors have reported consistent results including significant reduction in protein and ash contents and increase in moisture and lipid levels in WB muscles compared to their normal counterpart (Cai et al, 2018;Soglia et al, 2016a,b;Wold et al, 2017). The collagen content in the WB, SM, WB, WS/WB, and WS/SM presented contrasting results since some studies showed a higher content than the normal group and others did not observe a significant difference (Baldi et al, 2018;Cai et al, 2018;Soglia et al, 2016a,b).…”
Section: Physical-chemical Modifications In Abnormal Chicken Breastsmentioning
confidence: 78%
“…The weakness in the technique for detecting these myopathies is a key point and fast and nondestructive methods need to be developed and applied. On this regard, some successful attempts have been made, such as the application of radiofrequency spectra in the detection of WS in skin-on chicken carcasses (Traffano-Schiffo, Castro-Giraldez, Colom, & Fito, 2017) and the usage of near-infrared spectroscopy (NIR) for the detection of breast fillets chicken with WB (Wold, Måge, Løvland, Sanden, & Ofstad, 2018;Wold, Veiseth-Kent, Høst, & Løvland, 2017). Although the use of NIR in the detection of WB was effective, the technique was developed for breast fillet, and its efficacy in carcasses was not tested.…”
Section: Classification Of Myopathiesmentioning
confidence: 99%
“…27 The protein content in chicken sausages made with WB and/or N breast ranged from 16.01 to 17.48 g/100 g and no significant differences were found between formulations though those produced from WB muscles tended to have lower protein content. WBs have lower protein content than N breasts 2,8,16,28 as a result of myodegeneration of the muscle fibers. The protein degradation effect that occurs in WBs is probably counterbalanced in chicken sausage by the addition of soybean skin and protein, along with the effect of processing during the grinding, mixing and curing stages.…”
Section: Resultsmentioning
confidence: 99%
“…Dry weight was determined indirectly as 100%—% water content, where the % water content was determined according to NMKL 23 (NMKL ). Fat content was determined by NMR (Maran Ultra LF‐NMR; Oxford Instruments, Oxfordshire, UK), as described previously (Wold et al ). pH was measured by a pH meter (PHM210; Radiometer Analytical SAS, Villeurbanne, Cedex, France).…”
Section: Methodsmentioning
confidence: 99%